2(y+1)-5=7
2(y+1)=7+5
2(y+1)=12
2(y+1)/2=12/2
y+1=6
y=6-1
y=5
2006-09-17 07:28:35
·
answer #1
·
answered by Anonymous
·
1⤊
0⤋
y=5
2006-09-17 14:30:01
·
answer #2
·
answered by POPPY 5
·
0⤊
0⤋
y=5
2006-09-17 14:29:50
·
answer #3
·
answered by Mr. Truknit 4
·
0⤊
0⤋
2 (y+1)-5=7
2y=2-5=7
2y-3=7
2y=10 ===>
y=5
2006-09-17 14:25:39
·
answer #4
·
answered by alireza w 1
·
0⤊
0⤋
2y + 2 -5 = 7
2y -3 =7
2y = 7 +3
y= 10 / 2
y = 5
2006-09-17 14:29:57
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
2(y+1)-5 =7
2y+2-5=7
2y + - 3 =7
2y - -3 =7 +3
2y= 10
y =5
2006-09-17 14:30:35
·
answer #6
·
answered by bi_cali_chick86 2
·
0⤊
0⤋
2(y+1)-5 =7
2y+2-5=7
2y + - 3 =7
2y - -3 =7 +3
2y= 10
y =5
2006-09-17 14:25:11
·
answer #7
·
answered by C 2
·
0⤊
0⤋
2(y + 1) - 5 = 7
2(y + 1) = 12
y + 1 = 6
y = 5
2006-09-17 14:35:28
·
answer #8
·
answered by Sherman81 6
·
0⤊
0⤋
2y + 2 - 5= 7
2y - 3 = 7
2y= 10
y= 5
2006-09-17 14:32:12
·
answer #9
·
answered by Trish 2
·
0⤊
0⤋
the answer is 5
2006-09-17 14:27:29
·
answer #10
·
answered by bo_cloe 1
·
0⤊
0⤋